Lucky man a memoir - Fox, Michael J. 1961- (Hyperion, 2002)
With the same passion, humor, and energy that Fox has invested in his dozens of performances over the last 18 years, he tells the story of his life, his career, and his campaign to find a cure for Parkinsons.